Efficient nitrate removal using micro‐electrolysis with zero valent iron/activated carbon nanocomposite. Issue 12 (29th February 2016) - Liu, Guo; Zhou, Yaqi; Liu, Zhaoyang; Zhang, Junjie; Tang, Binbin; Yang, Shaogui; Sun, Cheng
ABSTRACT: BACKGROUND: Increasing nitrate concentration in ground water resources due to increased municipal and industrial contaminations is posing a great threat to human health worldwide. Therefore, an efficient technique to remove nitrate from ground water is in high demand. RESULT: In this study, nanoscale zero valent iron (NZVI)/activated carbon (AC) nanocomposite material was successfully synthesized to form a highly efficient micro‐galvanic cell to be used in the chemical reduction of nitrate. Analysis of NZVI‐AC composites were conducted by BET, XRD, SEM, TEM and XPS, while utilizing sodium borohydride as a reducing agent in liquid phase reaction for the reduction of ferrous ions. Several factors during the preparation process were investigated for their effect on the performance of the material when used for the reduction of nitrate in aqueous media. Experiment results demonstrated that the material prepared under optimized preparation conditions can remove up to 94.3% of nitrates with composites at 2.1 g L −1 . The final degradation products are mainly N2 and N H 4 + . CONCLUSION: The composites were found to behave more efficiently for nitrate removal when compared with NZVI. In addition, the production of these new composite materials can be economically scaled up as with NZVI, which is necessary for practical environmental remediation. © 2016 Society of Chemical Industry